2019
DOI: 10.1158/1078-0432.ccr-18-1965
|View full text |Cite
|
Sign up to set email alerts
|

The Senescence-associated Secretory Phenotype Mediates Oncogene-induced Senescence in Pediatric Pilocytic Astrocytoma

Abstract: Purpose: Pilocytic astrocytoma is the most common childhood brain tumor, characterized by constitutive MAPK activation. MAPK signaling induces oncogene-induced senescence (OIS), which may cause unpredictable growth behavior of pilocytic astrocytomas. The senescence-associated secretory phenotype (SASP) has been shown to regulate OIS, but its role in pilocytic astrocytoma remains unknown.Experimental Design: The patient-derived pilocytic astrocytoma cell culture model, DKFZ-BT66, was used to demonstrate presenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 55 publications
3
40
2
Order By: Relevance
“…These could include e.g. the inhibition of other MAPK-related survival pathways like AKT/mTOR [38], or the use of senolytic drugs [37], both of which remain to be introduced into the clinical treatment of pLGGs. PD was observed in 3/11 (27%) of the patients who stopped trametinib, within 4 months after EOT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These could include e.g. the inhibition of other MAPK-related survival pathways like AKT/mTOR [38], or the use of senolytic drugs [37], both of which remain to be introduced into the clinical treatment of pLGGs. PD was observed in 3/11 (27%) of the patients who stopped trametinib, within 4 months after EOT.…”
Section: Discussionmentioning
confidence: 99%
“…The low rates of CR indicate that parts of the tumor may not be targetable by the MEKi treatment alone, just as is the case with cytotoxic conventional chemotherapy. It is conceivable that this non-responding compartment, possibly quiescent through OIS and SASP [ 15 , 37 ], is the source of the progression observed in some patients after EOT with targeted treatments. Supplementary strategies will therefore be needed to implement additional therapeutic regimens to improve treatment outcome and PFS of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The number of senescent cells in tissues increases with age (Spaulding et al, 1997;Krishnamurthy et al, 2004;Herbig et al, 2006;Krizhanovsky et al, 2008;Vidal et al, 2012;Waaijer et al, 2012), and the rate of their accumulation predicts the lifespan of mice (Jurk et al, 2014). The secretions from senescent cells lead to a senescence-associated secretory phenotype (SASP), which might contribute to aging-associated tissue dysfunction or the development of a cancerous niche in old tissue (Coppe et al, 2010;Castro-Vega et al, 2015;Buhl et al, 2019;Lopes-Paciencia et al, 2019). A recent study showed that the transplantation of senescent cells into mice leads to the early onset of aging-related phenotypes (Xu et al, 2017(Xu et al, , 2018, which supports the current hypothesis that senescence can be a driver of aging (Krtolica et al, 2001;Sturmlechner et al, 2017;Lewis-McDougall et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations are the pure effect of tumor volume reduction, since we demonstrated that, preoperatively, smaller tumors grew at a slower rate. Secondly, it has been shown in a pilocytic astrocytoma cell model that mediators of inflammation such as interleukin-1b (IL-1b) did reduce cell growth via induction of senescence-associated secretory phenotype expression [45]. It is well known from pilocytic astrocytoma surgery that residual tumors often switch into senescence after resection despite significant growth prior to surgery.…”
Section: Results Of Growth Ratesmentioning
confidence: 99%